(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Diaspora may be defined as a group or groups of people dislocated from their homeland and then re-rooted in numerous homes on unfamiliar soil. Amitav Ghosh is one of the best-known postmodern writers. His topics are more unique and personal than others. His writings cover a variety of topics, including migration and diaspora, memory and history, political conflict and intergroup violence, love and grief, interpersonal interactions, and historical events. This paper analyses the displacement of characters like Tridib, the unnamed narrator, Thamma, Mayadebi, Ila, and May in the novel The Shadow Lines. This displacement creates a traumatic sense of dislocation, and migrants fail to integrate themselves into the alien land. War and partition are the primary causes of dislocation.